The Difference Chlorophyll of Wheat Grass (Triticum aestivum L.) Planted with Different Media - riska nur hayati; Elsa Yuniarti (Universitas Negeri Padang, 2020)
Planting media is a provider of nutrients that play an important role in increasing chlorophyll levels in plants. Wheat grass is one of the high chlorophyll plants and is beneficial for health. The purpose of this research was to determine the differences in the chlorophyll content of wheat grass grown with soil and charcoal media (hidroponik). The research was an experimental which was analyzed by the One Sample T-test at a significant level of 5%, conducted in February 2019 at the Biology Research Laboratory of the FMIPA UNP. Measuring chlorophyll levels using the Wintermans method with a leaf sample of 100 g which is 10 days old after planting. The results showed that there was a significant difference in the chlorophyll content of wheat grass which was planted with soil and charcoal media (hydroponic) media because of Sig. (2-tailed) which is 0,030<0,05 and the highest chlorophyll content is found in wheat grass planted with soil media.